2009
DOI: 10.1371/journal.pone.0005927
|View full text |Cite
|
Sign up to set email alerts
|

The Time-Course of Visual Categorizations: You Spot the Animal Faster than the Bird

Abstract: BackgroundSince the pioneering study by Rosch and colleagues in the 70s, it is commonly agreed that basic level perceptual categories (dog, chair…) are accessed faster than superordinate ones (animal, furniture…). Nevertheless, the speed at which objects presented in natural images can be processed in a rapid go/no-go visual superordinate categorization task has challenged this “basic level advantage”.Principal FindingsUsing the same task, we compared human processing speed when categorizing natural scenes as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
147
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(167 citation statements)
references
References 60 publications
(93 reference statements)
17
147
2
1
Order By: Relevance
“…However, there was some indication of superior performance in the natural-manmade group under processing time challenges (see Figure 5). This mirrors the results with human participants, where categorical distinctions between two members of the same superordinate category are more difficult than distinctions between members of two different superordinate categories, particularly with shorter processing times Loschky & Larson, 2010;Mace et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
“…However, there was some indication of superior performance in the natural-manmade group under processing time challenges (see Figure 5). This mirrors the results with human participants, where categorical distinctions between two members of the same superordinate category are more difficult than distinctions between members of two different superordinate categories, particularly with shorter processing times Loschky & Larson, 2010;Mace et al, 2009). …”
Section: Discussionsupporting
confidence: 81%
“…We replicated the advantage of superordinate object categorization over basic-level object categorization (Mace et al, 2009) and demonstrated that material classification was more similar to basic-level than to superordinate object categorization. The speed of categorization under these ultra-short presentation times was crucially mediated by our normalization procedure.…”
Section: Discussionmentioning
confidence: 53%
“…Mace, Joubert, Nespoulous, and Fabre- Thorpe (2009) reported increased reaction times in a go/no-go task if the target represented a basic-level category rather than a superordinate category. Thus, varying the level of abstraction in the objects should result in a variation of task difficulty.…”
Section: Experiments 1bmentioning
confidence: 99%
“…Le niveau de base est, en conséquence, le niveau le plus élevé (le plus abstrait) où les membres des catégories ont des formes globales perçues de façon similaire et où, du même coup, les catégories entre elles sont le mieux différenciées. Pour cette raison, il est réputé être le niveau d'entrée privilégié dans la catégorie, même si cela semble moins vrai pour des membres atypiques de celle-ci (Murphy & Brownell 1985) ou dans le cas de la catégorisation visuelle (Macé et al 2009). Il représente donc un optimum du point de vue de l'efficacité cognitive de la catégorisation.…”
unclassified